Chitin nanowhisker (ChNW)-functionalized electrospun PVDF membrane for enhanced removal of Indigo carmine. (1st June 2017) - Gopi, Sreerag; Balakrishnan, Preetha; Pius, Anitha; Thomas, Sabu
Graphical abstract: Highlights: For the first time, ChNW reinforced PVDF material developed by electrospinning technique. ChNW isolated by excluding proteins and minerals later, used for PVDF functionalization. ChNW tune the PVDF from hydrophobic to hydrophilic material and used for IC removal. The idea can be leads to various applications such as proteins, virus and hormones adsorption. Abstract: In this study, an active functional adsorbent membrane developed by combining both hydrophilic bio polymer filler such as chitin nanowhiskers ( ChNW ) which contains two functional groups and a hydrophobic polymer matrix such as polyvinylidene fluoride (PVDF) using electrospinning technique. Here ChNW were successfully extracted by excluding proteins and mineral and well characterized using FTIR, XRD, SEM and TEM. The optimized combination of PVDF/ChNW (15%:1%) membrane was fabricated and well characterized using SEM, water contact angle and FTIR spectroscopy. There was a remarkable difference in contact angle observed for PVDF/ChNW (22.72°) compared to neat PVDF (93.1°) membrane. Ultimately the membrane used for indigo carmine (IC) adsorption and an enhanced removal efficiency (88.9%) and adsorption capacity (72.6 mg g −1 ) were observed compared to neat PVDF. In the future, the overall idea can make leads to various applications such as proteins, virus and hormones adsorption from the contaminated sources.